An analysis of errors in using English articles by 10th graders at Quảng Xương III High School, Thanh Hóa Province. M.A Thesis Linguistics: 60 14 01 1 - Ngô, Thị Khuyên (University of Languages and International Studies, 2017)
This study aims at providing a comprehensive account of the types of errors produced by the 10th graders at Quảng Xương 3 High School (QXHS) in their use of articles, based on the Surface Structure Taxonomies (SST) of errors. Data were collected from written samples of 100 10th grade students at QXHS. The students were given forty-five minutes to write on one of four topics appropriate with their level. M.A Thesis English Teaching Methodology -- University of Languages and International studies. Vietnam National University, Hanoi, 2014